The Challenges of Teaching Grammar at the University Level: Learning From the Experience of English Lecturer - Tirza Kumayas; Fergina Lengkoan (Journal of English Culture, Language, Literature and Education, 2023)
Grammar overall, is a challenging language skill. Even experienced English lecturers may face difficulties in explaining grammar to students. Grammar is the primary skill to be developed when learning English as a foreign language. Yet, when other languages' skills gained more attention, grammar came to be seen as the least important skill. Without using proper assessment to reduce student understanding, this is frequently explained in a straightforward manner by means of other skills. This study focuses on the challenges English language teachers use when teaching grammar at the second-grade level. In this essay, every single English language teacher participates. The researchers interviewed them, copied, and analysed the data obtained from the interview. Problems and difficulties of students are no less important for lecturers to know in teaching grammatical structures. In this case, English lecturers are challenged to find more strategic and creative ways of teaching grammar. Mastery of good grammar guarantees students' ability to master other skills such as writing and speaking. Due to this, the study may benefit other English language teachers and lead to new ideas for addressing the problem at hand. Everyone agreed that she experienced three challenges while they were learning grammar. This study can be a good reference for other English lecturers and students, and parents in overcoming these challenges.